Dance therapy and cognitive impairment in older people: A review of clinical data - Menezes,Ana Clara (2022)
ABSTRACT The growing interest for nonpharmacological treatment alternatives to older people with mild cognitive impairment or dementia has increased exponentially for the past few years; in this context, dance therapy is an effective therapeutic tool in improving the cognition of older people. The aim of this study was to verify whether dance therapy is a viable tool in promoting benefits with regard to the cognition and mood of older people with cognitive impairment. A database search covering the past 10 years was carried out. Result: The search found 193 papers; after title, abstract, and duplicity analysis, 14 of those were selected, of which 10 were fully revised. The studies showed positive results regarding the improvement of cognitive function after dance stimulations, as well as beneficial effects on the mood of older people with cognitive impairment.